Economic growth, youth unemployment, and political and social instability: A study of policies and outcomes in post-Arab spring Egypt, Morocco, Jordan, and Tunisia - Heather Prince; Yara Halasa-Rappel; Amna Khan (United Nations Research Institute for Social Development (UNRISD), 2018)
The study has surveyed the post-Arab Spring youth employment policies that have been adopted in Egypt, Morocco, Jordan, and Tunisia. In addition, the study examines whether and how the economic policies implemented in these countries led to high levels of youth unemployment prior to the Arab Spring. It also analyses whether, after the conclusion of this series of massive social protests, new policies and institutions have emerged to provide innovative solutions that address the problem. While the topic of this study concerns youth employment policies, efforts have been made to briefly describe new or revised employment programmes as a means to illustrate the way in which these policies operate on implementation.
Keywords: 330